2007
DOI: 10.1128/aac.00601-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of the rapA Gene in Controlling Antibiotic Resistance of Escherichia coli Biofilms

Abstract: By using a high-throughput screening method, a mutant of a uropathogenic Escherichia coli strain affected in the rapA gene was isolated. The mutant formed normal-architecture biofilms but showed decreased penicillin G resistance, although the mutation did not affect planktonic cell resistance. Transcriptome analysis showed that 22 genes were down-regulated in the mutant biofilm. One of these genes was yhcQ, which encodes a putative multidrug resistance pump. Mutants with mutations in this gene also formed biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 39 publications
2
70
0
Order By: Relevance
“…In a uropathogenic E. coli strain, inactivation of the rapA gene, encoding a helicase-like protein, does not alter biofilm formation but increases susceptibility to penicillin G in biofilm cells. In biofilm cells of the rapA mutant, the expression levels of 22 genes are reduced, including those encoding a putative MDR pump (YhcQ), a putative carbohydrate transport and metabolism protein (YeeZ), and a transcriptional regulator (SdiA) (898). B. fragilis cells show elevated RND pump expression upon induction by bile salts and also increased possibility of biofilm formation (899).…”
Section: Role Of Efflux Pumps In Biofilm Formation and Resistancementioning
confidence: 99%
“…In a uropathogenic E. coli strain, inactivation of the rapA gene, encoding a helicase-like protein, does not alter biofilm formation but increases susceptibility to penicillin G in biofilm cells. In biofilm cells of the rapA mutant, the expression levels of 22 genes are reduced, including those encoding a putative MDR pump (YhcQ), a putative carbohydrate transport and metabolism protein (YeeZ), and a transcriptional regulator (SdiA) (898). B. fragilis cells show elevated RND pump expression upon induction by bile salts and also increased possibility of biofilm formation (899).…”
Section: Role Of Efflux Pumps In Biofilm Formation and Resistancementioning
confidence: 99%
“…High-thoughput screening of E. coli mutants showed that rapA mutants displayed decreased resistance toward penicillin, norfloxacin, chloramphenicol, and gentamicin (83). It was demonstrated that rapA not only regulates yhcQ, a gene encoding a putative multidrug resistance (MDR) pump, but also yeeZ, a gene suspected to be involved in ECM production (83).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…It was demonstrated that rapA not only regulates yhcQ, a gene encoding a putative multidrug resistance (MDR) pump, but also yeeZ, a gene suspected to be involved in ECM production (83). Thus, a dual rapA-mediated action was proposed, with efflux through a pump and reduced penetration through an increase in polysaccharide production (83).…”
Section: Biofilm Recalcitrance Is Multifactorialmentioning
confidence: 99%
“…However, a recent study suggested that MexAB-OprM and MexCD-OprJ are involved in biofilm resistance to the macrolide azithromycin (14). Furthermore, a putative multidrug efflux pump, YhcQ, has been implicated in Escherichia coli biofilm antibiotic resistance (23).…”
mentioning
confidence: 99%